Effects of Tax Audit on Revenue Generation - Endalew Gutu Tarfa; Genfure Tarekegn; Beyene Yosef (Journal of International Trade, Logistics and Law, 2020)
Taxation is a compulsory payment or transfer of resources from private to public sector levied on the basis of the determined criterion and without reference to specific benefits received in order to accomplish some of the nation’s economic and social objectives. The study was undertaken to address the tax audit practice in Jimma and Hawassa Branches of Federal Ministry of Revenue. To conduct the study a mixed method or quantitative and qualitative approach has been executed to address issues that could not be obtained by adopting a single method. Further, the study both descriptive and explanatory research design were employed. To achieve the objective of the study, purposive sampling techniques has been employed and the sample size was computed scientifically. Therefore, in order to address the research objective, the researchers used the survey data collected through questionnaires. The data collected via questionnaire has been analyzed with the aid of statistical software. Accordingly, SPSS Version 20.0 and Stata software have been employed. the study revealed that tax audit techniques applied and provision of training to the taxpayers are positive factors affecting the tax revenue generation significantly, on the contrary, an illegal practice of taxpayer is negative factor that affecting the tax revenue generation. It is recommended that ministry of revenue should consider factors affecting revenue generation.